Blunt scratch strength of polycrystalline alumina. Issue 1 (5th September 2017) - Cook, Robert F.
Abstract: A model for the fracture strength of brittle materials controlled by blunt (spherical) scratches is developed and compared with measurements on a polycrystalline alumina. The model is based on a residual stress‐intensity factor for median cracks at scratches that include a localized plastic deformation zone formed by dragged spherical contacts. The stress‐intensity factor depends nonlinearly on the normal contact load P, resulting in a predicted strength variation of P −3/4 . The strength result validates previous claims and extends the overall indentation‐strength framework. However, the result has only limited effectiveness in describing experimental measurements, pertaining only to ideal blunt scratches formed over a limited load domain.